2011
DOI: 10.1371/journal.pone.0025338
|View full text |Cite
|
Sign up to set email alerts
|

Oral Treatment with γ-Aminobutyric Acid Improves Glucose Tolerance and Insulin Sensitivity by Inhibiting Inflammation in High Fat Diet-Fed Mice

Abstract: Adipocyte and β-cell dysfunction and macrophage-related chronic inflammation are critical for the development of obesity-related insulin resistance and type 2 diabetes mellitus (T2DM), which can be negatively regulated by Tregs. Our previous studies and those of others have shown that activation of γ-aminobutyric acid (GABA) receptors inhibits inflammation in mice. However, whether GABA could modulate high fat diet (HFD)-induced obesity, glucose intolerance and insulin resistance has not been explored. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(137 citation statements)
references
References 32 publications
5
130
0
2
Order By: Relevance
“…Tian, et al [50], examined obesity and hyperglycemia in high fat diet-fed mice. In these mice obesity-related inflammation appears to be a major pathogenic factor.…”
Section: Studies In Humansmentioning
confidence: 99%
“…Tian, et al [50], examined obesity and hyperglycemia in high fat diet-fed mice. In these mice obesity-related inflammation appears to be a major pathogenic factor.…”
Section: Studies In Humansmentioning
confidence: 99%
“…In mice, we previously observed that it enhanced b-cell proliferation and reduced b-cell death, which reversed T1D (9). Indeed, in various disease models, GABA exerts trophic effects on b-cells and protects against diabetes (9,11). More recent studies reveal that GABA also protects human b-cells against apoptosis and increases their replication rate (12,13).…”
mentioning
confidence: 95%
“…It has paracrine and autocrine properties in various peripheral tissues (Watanabe et al, 2002). It has a role in the inhibition of many inflammatory cellular reactions (Tian et al, 2011) and has antidiabetic (Soltani et al, 2011), antioxidant, and free radical-scavenging properties (Deng et al, 2013). GABA is found all over the GI tract, in endocrine-like cells, and in enteric nerves, and it is considered as a neurotransmitter with an endocrine GI tract function (Hyland & Cryan, 2010).…”
Section: Introductionmentioning
confidence: 99%